Strategi Pemasaran Produk Café Batu Jimbar Sanur dalam Meningkatkan Kunjungan Wisatawan - Ni Kadek Dwi Kristina Aryani; I Gede Sutarya; Putu Kussa Laksana Utama (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2019)
Based on this research, Café Batu Jimbar has a pretty good potential but tourists visitingthe Café Batu Jimbar are still not optimal because of the intense competition in theculinary field, so that Café Batu Jimbar should be able to face competition by makingsuperior product marketing strategies. So, this research aims to determine themarketing strategy of Café Batu Jimbar Sanur product in increasing tourist visits. Themethod used in this research is descriptive qualitative and quantitative descriptivemethods using descriptive analysis or descriptive statistics. Data collected throughobservation, interviews, questionnaires, literature study, and documentation. Then thedata were analyzed using IFAS and EFAS matrix analysis and SWOT analysis. Theresults of this study indicate that the products offered at the Café Batu Jimbar are quite diverse, the product marketing strategy used by the Café Batu Jimbar has disadvantages such as the products offered more to foreign tourists, besides that the strengths of CaféBatu Jimbar have cooperation with the travel agent so that it helps in increasing tourist visits, as well as unfavorable tourist perceptions of the relatively expensive prices of food and beverage products. Therefore, the marketing strategy of Café Batu JimbarSanur products in increasing tourist visits is recommended using alternative strategies that have been formulated in this research.